2003
DOI: 10.1002/jcb.10746
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cells induce osteoblast apoptosis: A possible contributor to bone degradation

Abstract: Breast cancer cells exhibit a predilection for metastasis to bone. There, the metastases usually bring about bone loss with accompanying pain and loss of function. One way that breast cancer cells disrupt the normal pattern of bone remodeling is by activating osteoclasts, the bone degrading cells. Nevertheless, targeting the osteoclasts does not cure the disease or result in bone repair. These observations indicate that osteoblast function also may be compromised. The objective of this study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 36 publications
4
67
1
1
Order By: Relevance
“…Moreover, we have shown that NOG is a driver of this effect because the activation was observed in the presence of NOG and it was lost when NOG was depleted. Previous studies have shown that conditioned medium of MDA-231 breast cancer cells induce osteoblast apoptosis in vitro (35,36), which under certain circumstances might add on the NOG phenotype described herein.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, we have shown that NOG is a driver of this effect because the activation was observed in the presence of NOG and it was lost when NOG was depleted. Previous studies have shown that conditioned medium of MDA-231 breast cancer cells induce osteoblast apoptosis in vitro (35,36), which under certain circumstances might add on the NOG phenotype described herein.…”
Section: Discussionmentioning
confidence: 73%
“…In particular, tumor cell activation of osteoclasts via the ''vicious cycle'' of secretion of PTHrP or RANK ligand has been implicated in bone resorption (4,19,42). However, we previously hypothesized that the balance of bone deposition and resorption could be altered as well by reducing osteoblast number or differentiation and/or activity (33). In vitro coculture of metastatic human breast carcinoma cells or their conditioned medium with human osteoblasts resulted in apoptosis of the osteoblasts (33).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, tumor cell activation of osteoclasts via the ''vicious cycle'' of secretion of PTHrP or RANK ligand has been implicated in bone resorption (4,19,42). However, we previously hypothesized that the balance of bone deposition and resorption could be altered as well by reducing osteoblast number or differentiation and/or activity (33). In vitro coculture of metastatic human breast carcinoma cells or their conditioned medium with human osteoblasts resulted in apoptosis of the osteoblasts (33).…”
Section: Discussionmentioning
confidence: 99%